A novel control strategy for power quality improvement in grid-connected solar photovoltaic system - Pankaj Gakhar; Manoj Gupta (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this paper, a novel and dynamic, current control based inverter control strategy has been used for energy optimization and power quality improvement in a grid-connected solar photovoltaic plant using a PI controller. The output of the plant is delivered to the grid passing through a boost converter controlled by an MPPT controller and an inverter. The control strategy proposed offers the flexibility to keep control of active as well as reactive power being injected straight into the grid and also helps in mitigating the total harmonic distortion levels. Also, the effect of the conventional PI controller and PI controller optimized through Genetic Algorithm has been compared. The GA-PI controller has been found effective in reducing the Total Harmonic Distortion in the current injected in the grid. The effectiveness of the work has been observed by using a MATLAB/SIMULINK environment.